2017
DOI: 10.1111/irfi.12120
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Relationship between Investors' Sentiment and Stock Returns: Evidence from a Quantile Non‐causality Test

Abstract: This study investigates the causal relationship between investor sentiment and stock returns in the USA by conducting a quantile Granger non‐causality test. Employing two proxies for investor sentiment – the sentiment index developed by Baker and Wurgler in 2007 and the University of Michigan Consumer Survey, a consumer confidence index – we find that the causal relationship between investor sentiment and stock returns strengthens when a tail quantile interval is considered. This finding implies that the inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 35 publications
2
18
0
1
Order By: Relevance
“…In this sense, Kim and Kim (2014) confirmed stock price performance's positive influence on investor sentiment, and Piñeiro-Chousa et al (2016) showed that Tobin's Q, P/E ratio and capitalisation are related to increases in microblogging investor sentiment. Therefore, these results suggest the existence of a causal relationship between investor sentiment and stock market activity (Li, Guo & Park, 2017).…”
Section: Literature Reviewmentioning
confidence: 64%
“…In this sense, Kim and Kim (2014) confirmed stock price performance's positive influence on investor sentiment, and Piñeiro-Chousa et al (2016) showed that Tobin's Q, P/E ratio and capitalisation are related to increases in microblogging investor sentiment. Therefore, these results suggest the existence of a causal relationship between investor sentiment and stock market activity (Li, Guo & Park, 2017).…”
Section: Literature Reviewmentioning
confidence: 64%
“…Ni et al (2015) used panel quantile regression and found that influence of investor sentiment on stock returns is asymmetric. Li et al (2017) applied Quantile Causality test and suggested that the predictability of sentiment is more marked under extreme market situations. Ma et al (2018) applied quantile regression and found that sentiment predicts stock return only at lower quantiles and not at higher quantiles…”
Section: Literature Reviewmentioning
confidence: 99%
“…The index has proven to be one of the most influential variables in consumption decisions and in the economic situation (Bock Eastman, & McKay, 2014;Sorić, 2018). Consumer confidence is influenced by their personal finances and the economic environment, macroeconomic conditions and the business situation (Ferrer et al 2016;Salhin, Sherif, & Jones, 2016;Li, Guo, & Park, 2017).…”
Section: Consumer Confidence Indexmentioning
confidence: 99%
“…From the logit model, the pandemic situation is significantly influencing the changes in investor confidence in the Islamic financial market. Consumer confidence is influenced by their personal finances, economic environment, macroeconomic condition and business situation (Ferrer et al, 2016;Salhin et al, 2016;Li et al, 2017).…”
Section: Probit Logit Model Robustness Standard Errormentioning
confidence: 99%